2016
DOI: 10.1007/s10753-016-0449-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the NLRP3 Inflammasome Is Associated with Valosin-Containing Protein Myopathy

Abstract: Aberrant activation of the NOD-like receptor (NLR) family, pyrin domain-containing protein 3 (NLRP3) inflammasome triggers a pathogenic inflammatory response in many inherited neurodegenerative disorders. Inflammation has recently been associated with Valosin Containing Protein (VCP)-associated diseases, caused by missense mutations in the VCP gene. This prompted us to investigate whether NLRP3 inflammasome plays a role in VCP-associated diseases, which classically affects the muscles, bones and brain. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 87 publications
1
27
0
Order By: Relevance
“… 37 , 38 Mcc950 not only inhibited NLRP3 inflammasome activation as evidenced by suppressing cleavage of caspase 1 and downstream interleukin IL-1 β production, but decreased apoptosis and mature IL-1 β released by HRECs. Thus, Mcc950 has an anti-inflammatory role in the pathogenesis of impaired glucose-mediated retinopathy, and these data agree with previous reports that Mcc950 can inhibit NLRP3 inflammasome activation in dermal and pulmonary inflammation, 31 crystal-induced kidney fibrosis, 33 valosin-containing protein-associated diseases, 32 cryopyrin-associated periodic syndromes, 20 , 39 , 40 hypertension, 41 and myocardial infarction. 42 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 37 , 38 Mcc950 not only inhibited NLRP3 inflammasome activation as evidenced by suppressing cleavage of caspase 1 and downstream interleukin IL-1 β production, but decreased apoptosis and mature IL-1 β released by HRECs. Thus, Mcc950 has an anti-inflammatory role in the pathogenesis of impaired glucose-mediated retinopathy, and these data agree with previous reports that Mcc950 can inhibit NLRP3 inflammasome activation in dermal and pulmonary inflammation, 31 crystal-induced kidney fibrosis, 33 valosin-containing protein-associated diseases, 32 cryopyrin-associated periodic syndromes, 20 , 39 , 40 hypertension, 41 and myocardial infarction. 42 …”
Section: Discussionsupporting
confidence: 92%
“…Activation of the NLRP3 inflammasome is thought to be key for the progression of pro-inflammatory effects of retinopathy including age-related macular degeneration 18 and DR. 27 Using immunofluorescence and western blot we confirmed NLRP3 inflammasome activation in human REC of proliferative membranes, a crucial characteristic of PDR. 28 , 29 , 30 The anti-NLRP3 inflammasome effect of Mcc950 for macrophages, microglia, myoblasts and dendritic cells is well described, 31 , 32 , 33 , 34 but its effect on inflammation of HRECs is unexplored. Thus, we investigated the potency of Mcc950 for attenuating inflammation in HRECs induced by high glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Recent mouse models of VCP showed that activation of the NLRP3 inflammasome is associated with VCP protein myopathy. Nalbandian et al (2017) reported a significant increase in the expression of NLRP3, Caspase 1, IL-1β, and IL-18 in the quadriceps of 12 and 24 months old VCPR155H/+heterozygous mice. Furthermore, a significant increase of IL-1β(+)F4/80(+)Ly6C(+) macrophages in the quadriceps and bones of the same mice were also observed and is positively correlated with high expression levels of TDP-43 and p62/SQSTM1 markers of VCP pathology and progressive muscle wasting (Nalbandian et al, 2017).…”
Section: Valosin Containing Protein (Vcp)mentioning
confidence: 95%
“…Over the past two decades, inflammation in PD has received great interest by many researchers, highlighting microglial activation, cytokine production and oxidative damage in the in vivo model and post-mortem [ 4 , 5 ]. Therefore, neuroinflammation represents a key role in the progressive degeneration of dopaminergic neurons and in the pathogenesis of PD [ 6 , 7 ]. This is demonstrated by the discovery of high levels of some proinflammatory cytokines, such as interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and many others, in the samples of the brain parenchyma and cerebrospinal fluid of affected patients from PD compared to control samples [ 8 ].…”
Section: Introductionmentioning
confidence: 99%